2023
DOI: 10.2147/idr.s400772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial Products for Colistin and Polymyxin B Susceptibility Testing for mcr-Positive and Negative Escherichia coli and Klebsiella pneumoniae in China

Abstract: To evaluate the performance of five widespread commercial products for colistin and polymyxin B susceptibility testing in China for mcr-positive and -negative Escherichia coli and Klebsiella pneumoniae. Methods: A total of 132 E. coli and 83 K. pneumoniae strains (including 68 mcr-1-positive E. coli and 28 mcr-8-positive K. pneumoniae) were collected. We analysed the performance of colistin susceptibility (with Vitek 2 and Phoenix M50) and the performance of polymyxin B susceptibility (with DL-96II, MA120, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…VITEK 2 ® COMPACT (BioMérieux, St. Louis, MO, USA) and Phoenix™ M50 (Becton Dickson Diagnostics, Franklin Lakes, NJ, USA) are the most widely used microbial identification and drug susceptibility analysis systems in the world [ 24 , 25 ]. The performance of these systems was tested against polymyxins in 132 strains of E. coli and 83 strains of K. pneumoniae , including strains positive for the mcr-1 and mcr-8 genes.…”
Section: Phenotypic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VITEK 2 ® COMPACT (BioMérieux, St. Louis, MO, USA) and Phoenix™ M50 (Becton Dickson Diagnostics, Franklin Lakes, NJ, USA) are the most widely used microbial identification and drug susceptibility analysis systems in the world [ 24 , 25 ]. The performance of these systems was tested against polymyxins in 132 strains of E. coli and 83 strains of K. pneumoniae , including strains positive for the mcr-1 and mcr-8 genes.…”
Section: Phenotypic Methodsmentioning
confidence: 99%
“…However, the systems exhibited unacceptable rates of CAs, EAs, and false-susceptible results, especially with K. pneumoniae isolates. Furthermore, the systems did not demonstrate good performance for detecting strains with the mcr-8 gene [ 24 ].…”
Section: Phenotypic Methodsmentioning
confidence: 99%
“…For colistin, a warning on the accuracy of several commercial systems for MIC results was previously issued by EUCAST, although it did not specifically evaluate the BD Phoenix M50 [68,69]. Recent studies indicate that the BD Phoenix M50 can produce accurate MIC results for colistin [70][71][72], and this has led to its inclusion in this study. The resistance to colistin in E. coli from chickens (6.6%) in this study was higher than that reported in many European countries where resistance is usually less than 1% [73][74][75], but resistance was lower than that reported in other parts of Asia [76].…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…By applying the Vitek 2 system, clinicians can recognize various types of bacteria, both gram-positive and gram-negative, allowing them to provide effective and targeted therapies for infections. Its effectiveness and speed make it a vital instrument in diagnosing and treating infectious ailments, which is why it is increasingly used in clinical settings globally [15,16]. Overall, the isolation and identification of pathogenic bacteria in wastewater effluent from butcher shops, and their antibiotic susceptibility profiling, are crucial for preventing the spread of antibiotic resistance and ensuring public health.…”
Section: Introductionmentioning
confidence: 99%